Empower HER Health: A Comparative Study on Women's Empowerment and Gender-Based Violence in Karnataka and India Using NFHS 4 And 5 - Namratha Kulkarni; Rizwana B Shaikh (Medsci Publications, 2024)
Introduction: Women's empowerment is crucial for gender equality. This study, utilizing NFHS 4 and 5 data, assesses GBV and women's empowerment, including health indicators in Karnataka and India, aiming to evaluate achievements and challenges impacting women's lives for gender equality. Materials and Methods: This study retrospectively analyzed NFHS 4 (2015-16) and NFHS 5 (2019-21) data for India and Karnataka, covering health, Gender-based Violence, education, economic and social-political empowerment. Data analysis used MS Excel 365 and Datawrapper tools. Results: Karnataka's female population increased by 7% (NFHS4 to NFHS5), surpassing India's 1%. Health indicators improved, including menstrual hygiene, family planning, prenatal and postnatal care, and reduced early marriages. Educational attainment, economic involvement, mobile phone ownership, and women's participation in household decisions increased. However, Karnataka saw a notable rise in GBV cases among young women, with spousal violence at 44.4% and sexual violence at 11% (NFHS5). Conclusion: This study depicts the evolution of women's empowerment and gender-based violence in Karnataka, India. Results show improvements in health, education, economic involvement, and specific empowerment indicators. However, the documented rise in GBV cases in Karnataka highlights the need for targeted interventions. Karnataka's experience can be a blueprint for achieving gender equality and women's empowerment in India.